Understanding marine dissolved organic matter production: Compositional insights from axenic cultures of Thalassiosira pseudonana. (11th July 2016) - Saad, Emily M.; Longo, Amelia F.; Chambers, Luke R.; Huang, Rixiang; Benitez‐Nelson, Claudia; Dyhrman, Sonya T.; Diaz, Julia M.; Tang, Yuanzhi; Ingall, Ellery D.
Abstract: Marine dissolved organic matter (DOM) is a key source of carbon and nutrients to microbial life in the oceans, but rapid biological utilization of labile DOM confounds its compositional characterization. In order to characterize potentially bioavailable DOM produced by phytoplankton, DOM from axenic cultures of Thalassiosira pseudonana cultivated in phosphorus (P) replete and low P conditions was extracted using high‐recovery electrodialysis (ED) techniques, which resulted in an average dissolved organic carbon (DOC) recovery of 76% ± 7% from all cultures. Low P concentrations resulted in greater cell‐normalized production of DOC relative to P replete culture controls at the same growth phase. Despite the different nutrient conditions, DOC composition and DOM molar ratios of carbon to nitrogen (C : N) were similar in all cultures. In contrast, low P concentrations influenced DOM molar carbon to phosphorus (C : P) ratios and dissolved organic phosphorus (DOP) composition. Under P replete and low P conditions, DOM C : P ratios were 130 (± 22) and 2446 (± 519), respectively. 31 P Nuclear Magnetic Resonance (NMR) spectroscopy identified P esters (> 90% of DOP) as the dominant P species in DOM produced under P replete conditions, with small or negligible contributions from phosphonates or glycerol P and polyphosphates. However, based on direct fluorometric analysis, DOP from low P cultures was greater than 8 times enriched in dissolved polyphosphate compared to DOP from replete cultures, which is consistent with the growing evidence that polyphosphate is a dynamic component of total P in low P ocean regions.